Research efforts and challenges in crowd-based requirements engineering: A review - Ahmad, Sabrina; Asmai, Siti Azirah; Abdullah, Rosmiza Wahida; Seok, Won Lee; Mat Zain, Zarina (Science and Information Organization, 2021)
Eliciting software system development requirements is a challenging task as the information is from various resources. The most constructive resource is the stakeholders of the system to be developed. It is critical yet time-consuming to capture essential requirements to realize a reliable and workable software system. The crowd-based Requirements Engineering (crowd-based RE) approach adapts the crowdsourcing technique to access an extensive range of stakeholders and save time, especially for the generic type system with no clear stakeholder. This paper presents current research efforts and challenges in crowd-based RE. A systematic literature review method is adopted to explore literature based on two specific research questions. The first question aimed at identifying research efforts on crowd-based RE, and the second question focused on the main challenges discovered in pursuing crowd-based RE. The findings from the literature review show that many efforts have been made to explore and further improve crowd-based RE. This paper provides a foundation to pursue research in improving crowdsourcing techniques for the benefit of requirements engineering.